Nurturing religious character: The impact of boarding school system at an Islamic state junior high school - Fadhlurrohman, Muhammad; Najiah, Fikrotun (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
In recent times, various negative occurrences within the Indonesian educational landscape, particularly concerning delinquency and the moral decay among adolescents, have raised concerns, especially at the Junior High School level. Islamic Boarding Schools have emerged as a solution sought by parents to provide a more comprehensive and holistic education for their children. This study aimed to explore the implementation of the Islamic Boarding School system in cultivating the religious character of students at MTs Negeri 1 Tegal. The research employed a qualitative descriptive approach, utilizing data collection methods such as interviews, observations, and documentation. Both primary and secondary data sources were utilized, with primary data acquired through a blend of observational techniques and interviews. Secondary data sources included curriculum records, participant rosters, infrastructure assessments, and activity documentation. Data analysis was conducted using the Miles and Huberman model, involving processes of data reduction, presentation, and drawing conclusions. To ensure data credibility, triangulation of sources, techniques, and time frames was employed. The findings indicate that the management of the Islamic Boarding School system at MTs Negeri 1 Tegal has been effective, encompassing planning, implementation, and evaluation stages. Moreover, the participation in the program has contributed to an enhancement in the religious character of the students. This study concludes that the Islamic Boarding School system at MTs Negeri 1 Tegal holds potential in shaping the religious character of students and could serve as a model for other educational institutions seeking to develop similar programs.